Assessment of community hospital disaster preparedness in New York State - Vick, MD, MBA, DHA, Dan J.; Wilson, PhD, DHA, Asa B.; Fisher, DBA, Michael; Roseamelia, PhD, Carrie (Journal of Emergency Management, 2018)
Objective: The intent of this study was to assess disaster preparedness in community hospitals across New York. Design: Descriptive and analytical cross-sectional survey study. The survey instrument consisted of 35 questions that examined six elements of disaster preparedness: disaster plan development, onsite surge capacity, available materials and resources, disaster education and training, disaster preparedness funding levels, and perception of disaster preparedness. Setting: Community hospitals in New York. Subjects: Contact information was obtained for 207 of 208 community hospitals. Email invitations to participate in the survey were sent to hospital CEOs and disaster preparedness coordinators. Completed surveys were received from 80 hospitals. Main Outcome Measures: Hospital responses to questions related to the six elements of disaster preparedness. Results: Most (87.5 percent) hospitals had experienced a disaster event during the past 5 years (2012-2016). Eighty percent had disaster plans that addressed all of six major types of disasters. Only 17.5 percent believed their disaster plans were “very sufficient” and did not require any revisions. Nearly three-quarters (73.3 percent) of hospitals could continue operations for less than a week without external resources. Less than half (49.4 percent) reported being satisfied or very satisfied with the level of funding that they received from the Hospital Preparedness Program. Most (88.8 percent) respondents felt that barriers to disaster preparedness exist for their organizations. Conclusions: The results demonstrate the current level of disaster preparedness among New York hospitals. The study’s approach is discussed as a model that will enable hospitals to identify focus areas for improvement and opportunities for legislation and advocacy.